2014
DOI: 10.1093/hmg/ddu212
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of epigenetic mediator expression and function in mouse and human embryonic blastomeres

Abstract: A map of human embryo development that combines imaging, molecular, genetic and epigenetic data for comparisons to other species and across pathologies would be greatly beneficial for basic science and clinical applications. Here, we compared mRNA and protein expression of key mediators of DNA methylation and histone modifications between mouse and human embryos, embryos from fertile/infertile couples, and following growth factor supplementation. We observed that individual mouse and human embryos are characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 76 publications
0
27
0
Order By: Relevance
“…Increasing challenges are anticipated in establishing transgenerational epigenetic inheritance in humans. Differences in epigenomes between mice and humans may not allow a direct extrapolation of data from mouse models [207]. Additionally, genetics may contribute to changing the epigenetic landscape through multiple human generations [207].…”
Section: Transgenerational Epigenetic Inheritance Of Environmentalmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing challenges are anticipated in establishing transgenerational epigenetic inheritance in humans. Differences in epigenomes between mice and humans may not allow a direct extrapolation of data from mouse models [207]. Additionally, genetics may contribute to changing the epigenetic landscape through multiple human generations [207].…”
Section: Transgenerational Epigenetic Inheritance Of Environmentalmentioning
confidence: 99%
“…Differences in epigenomes between mice and humans may not allow a direct extrapolation of data from mouse models [207]. Additionally, genetics may contribute to changing the epigenetic landscape through multiple human generations [207]. Therefore, genetic variations in human populations will always be confounding factor for studying transgenerational epigenetic inheritance in humans [206].…”
Section: Transgenerational Epigenetic Inheritance Of Environmentalmentioning
confidence: 99%
“…However, a recent study indicates that the formation of micro- and multiple-nuclei (multi-nuclei) can be induced in mouse embryos by disrupting the function of particular cell cycle proteins critical for developmental progression. Chavez and colleagues (2014) determined that translational block of Rps6ka4/Msk2 , a mitogenic factor known to be involved in the G1 phase of the cell cycle (Bettencourt-Dias et al 2004), in mouse zygotes resulted in the appearance of multiple micro- or multi-nuclei at the cleavage stage. In addition, increased blastomere movement and lysis, resembling cellular events described during mitotic catastrophe (Vakifahmetoglu et al 2008), was also observed in mouse embryos following mitotic arrest at the 3- to 8-cell stage.…”
Section: Aneuploidy Tolerance and Rescuementioning
confidence: 99%
“…Most studies have been performed in mouse models, and only a few in humans. Since differences in epigenetic regulation between mice and humans during pre-implantation development have been observed [141] , findings from mice and other species may not translate to humans directly. Moreover, many epigenetic factors, such as hydroxymethylation, long non-coding RNAs, and most of the histone modifications other than acetylation, have not been studied in the context of circadian regulation in humans.…”
Section: Epigenetic Factors Regulate Circadian Rhythmsmentioning
confidence: 99%